2022
DOI: 10.1111/iju.15046
|View full text |Cite
|
Sign up to set email alerts
|

PDE5 inhibitors and male reproduction: Is there a place for PDE5 inhibitors in infertility clinics or andrology laboratories?

Abstract: The objective of this review study is to evaluate the therapeutic role of PDE5 inhibitors (PDE5is) in the amelioration of oligoasthenospermia in infertile males. PDE5is have a beneficial influence on the secretory function of the Leydig and Sertoli cells, the biochemical environment within the seminiferous tubule, the contractility of the testicular tunica albuginea, and the prostatic secretory function. In several studies, the overall effect of sildenafil and vardenafil increased quantitative and qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 126 publications
(322 reference statements)
0
3
0
Order By: Relevance
“…Urologists can prescribe a range of medications to address these issues. For erectile dysfunction, treatments may include phosphodiesterase type 5 inhibitors (PDE5is) like sildenafil and vardenafil, which enhance the effects of nitric oxide, a natural chemical the body produces to relax penis muscles and increase blood flow [149,150].…”
Section: Addressing Erectile Dysfunction and Premature Ejaculation Fo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Urologists can prescribe a range of medications to address these issues. For erectile dysfunction, treatments may include phosphodiesterase type 5 inhibitors (PDE5is) like sildenafil and vardenafil, which enhance the effects of nitric oxide, a natural chemical the body produces to relax penis muscles and increase blood flow [149,150].…”
Section: Addressing Erectile Dysfunction and Premature Ejaculation Fo...mentioning
confidence: 99%
“…Their research revealed that PDE5is had a positive impact on the secretory function of Leydig and Sertoli cells and were linked to the regulation of contractility in the tunica albuginea of the testes and epididymis. Moreover, PDE5is have been shown to enhance sperm motility by augmenting prostatic secretory activity and to play a pivotal role in the regulation of sperm capacitation [150].…”
Section: Addressing Erectile Dysfunction and Premature Ejaculation Fo...mentioning
confidence: 99%
“…In this context, male infertility occurs in 30–50% of cases [ 3 ]. Varicocele, smoking, radiation, urinary tract infection, nutritional deficiencies, oxidative stress, and environmental factors are some reasons for male factors [ 4 , 5 , 6 ] but seem not to be completely understood in all aspects. Oxidative stress (OS) may play an increasingly important role in environmental factors when the production of reactive oxygen species (ROS) exceeds the body’s natural antioxidant neutralizing capacity [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%